Strategi Pemasaran Jasa Foto Produk Pada Photolog Studio Malang Dengan Menggunakan Analisis SWOT - Putra Perdana, Dimas Akbar; Mawardi, M. Cholid; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
AbstractÂ This study aims to analyze the marketing strategy of product photography services at Photolog Studio Malang using SWOT analysis. SWOT analysis is utilized to identify the strengths, weaknesses, opportunities, and threats facing the company. Data collection was conducted through observation and documentation techniques. The method used is qualitative descriptive. The results of the SWOT analysis reveal that the main internal strengths are the quality of services, affordable pricing, and service flexibility. The weaknesses include the lack of activity reports and organized financial management, as well as irregular promotional intensity. The internal opportunity factor is high market demand due to increasing awareness among business owners about the need for attractive product presentations. The main threats are incomplete production equipment and the rising number of competing service providers. It is hoped that the results of this study can serve as supporting data for optimal decision-making to enhance the sales of product photography services at Photolog Studio Malang.Â Keywords : Strategy, Product Photography Service Marketing, SWOT Analysis